Responses of sericotropin to toxic and pathogenic challenges: possible role in defense of the wax moth Galleria mellonella - Shaik, Haq Abdul; Mishra, Archana; Sehadová, Hana; Kodrík, Dalibor (Comparative biochemistry and physiology. Toxicology & pharmacology, 2020)
This study describes defense functions of the insect neuropeptide sericotropin, which is recognized as an agent that stimulates silk production in some lepidopteran larvae. Sericotropin, expressed in brain tissue of the wax moth Galleria mellonella in all developmental stages, is not expressed in silk glands, indicating its tissue specificity. Fluorescence microscopy confirmed the presence of sericotropin in the brain-subesophageal complex being predominantly and densely distributed under the plasmatic membrane and in axonal parts of neurons. Injection of venom from Habrobracon hebetor and topical application of the entomopathogenic nematode (EPN) Steinernema carpocapsae with symbiotic bacteria Xenorhabdus spp. into or onto G. mellonella larvae resulted in upregulation of the sericotropin gene and peptide, suggesting a role for sericotropin in defense and immunity. Accordingly, two synthetic fragments of sericotropin killed entomotoxic Xenorhabdus spp. bacteria in a disc diffusion antimicrobial test. Further, total metabolism, monitored by carbon dioxide production, significantly decreased after application of either venom or EPN, probably because of muscle impairment by the venom and serious cell damage caused by EPN, especially in the midgut. Both venom and EPN upregulated expression of genes encoding antimicrobial peptides gallerimycin and galiomicin in Galleria brain; however, they downregulated prophenoloxidase and phenoloxidase activity in hemolymph. These results suggest that sericotropin is a multifunctional peptide that plays an important role in G. mellonella defense and immunity.
Keywords: Moths; Gene Expression Regulation; vosí jedy; mužské pohlaví; Defense; Habrobracon hebetor venom; Insect brain; Antimicrobial activity; neuropeptidy; Entomopathogenic nematode; můry; regulace genové exprese; Nematoda; Neuropeptides; ženské pohlaví; zvířata; Host-Parasite Interactions; Wasp Venoms; larva; interakce hostitele a parazita; hlístice; Larva; Female; Male; Animals